Internet connectivity disruption in Ecuador (Ecuador) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Ecuador. Data sourced from IODA.
Network Disruption Incident ID: EC-2026-0029. Severity: critical. Confidence: 65%